Association of Puerperal Sepsis with Income Level, Booking Status, and Mode of Delivery Among Patients at A Tertiary Care Setting: Puerperal Sepsis with Income Level, Booking Status, and Mode of Delivery - Kumari, Sandhya; Bakhtawar, Samreen; Samo, Rukhsar; Nagdev, Suraksha; Abro, Shaista Hifaz; Shahani, Muhammad Parial (Pakistan Journal of Health Sciences, 2026)
According to the World Health Organization (WHO), puerperal sepsis is a contracted infection of the genital tract that occurs during labor or in a period of 42 days following the birth. It is the leading cause of preventable maternal disease and death in rich and poor countries. In Pakistan, it ranks third after hemorrhage and hypertensive diseases among women. Objectives: To determine the association of puerperal sepsis with booking status and mode of delivery among patients admitted at the Department of Obstetrics, Shaikh Zaid Women Hospital, Larkana. Methods: The study included 170 patients with puerperal sepsis in total. Demographic data were collected, including age, parity, socioeconomic position, and time since delivery. All the collected data were entered and analyzed using SPSS version 26.0. Results: According to the findings of this study, the mean age was 28.96 ± 6.41 years, the mean time since delivery was 22.11 ± 5.68 days, the mean parity was 1.58 ± 0.895, and the mean BMI was 24.51 ± 4.43. 103 (60.59%) patients were primigravida. 81 (47.65%) patients reported a monthly income of less than 50 thousand, and 81 (47.65%) patients reported a delay of more than 28 days. The income level (p-value=0.018) and mode of delivery (p-value=0.04) were found to have a significant association with puerperal sepsis. Conclusions: The puerperal sepsis is found to have a significant association with the caesarean section deliveries, income level, and case which remain un-booked during pregnancy.